Analysis of Factors Associated with Work Stress on Teachers of the Asuhan Kasih Special School and the State Special School of Pembina Kupang - Leonardus Nusi; Noorce Ch. Berek; Agus Setyobudi (Universitas Nusa Cendana, 2021)
Abstract. Job stress is a form of a person's response both physically and mentally to a change in his environment that is felt to be disturbing and causes him to be threatened or uncomfortable. The purpose of this study was to analyze the factors associated with work stress on teachers of the Asuhan Kasih Special School and the Pembina Kupang State Special School. The sampling technique used is simple random sampling with a sample of 47 subjects. The analysis in this study uses the Chi-Square test and Fisher Probability Exact Test as an alternative test. The results showed that there was a relationship between tenure (pvalue = 0.007), personality type (p-value = 0.002), and workload (p-value = 0.003) with work stress and there was no relationship between gender (p-value = 1000) and age (p-value). = 1000). = 0.379) with work stress on teachers of the Asuhan Kasih Special School and the Pembina State Special School of Kupang. Schools should conduct training in accordance with the responsibilities of each teacher and divide the number of students handled according to applicable regulations.